Surgical Treatment of Chronic Parotitis - Lans,Rik Johannes Leonardus van der (2019)
Abstract Introduction chronic parotitis (CP) is a hindering, recurring inflammatory ailment that eventually leads to the destruction of the parotid gland. When conservative measures and sialendoscopy fail, parotidectomy can be indicated. Objective to evaluate the efficacy and safety of parotidectomy as a treatment for CP unresponsive to conservative therapy, and to compare superficial and near-total parotidectomy (SP and NTP). Methods retrospective consecutive case series of patients who underwent parotidectomy for CP between January 1999 and May 2012. The primary outcome variables were recurrence, patient contentment, transient and permanent facial nerve palsy and Frey syndrome. The categorical variables were analyzed using the two-sided Fisher exact test. Alongside, an elaborate review of the current literature was conducted. Results a total of 46 parotidectomies were performed on 37 patients with CP. Neartotal parotidectomy was performed in 41 and SP in 5 cases. Eighty-four percent of patients was available for the telephone questionnaire (31 patients, 40 parotidectomies) with a mean follow-up period of 6,2 years. Treatment was successful in 40/46 parotidectomies (87%) and 95% of the patients were content with the result. The incidence of permanent and transient facial nerve palsy was 0 (0%) and 12 (26.1%), respectively. Frey syndrome manifested in 20 (43.5%) patients. Neither this study nor careful review of the current literature resulted in evident difference between SP and NTP regarding the primary outcome variables. Conclusion parotidectomy is a safe and effective treatment for CP in case conservative therapy fails. There is no evidence of a distinct difference between SP and NTP regarding efficiency, facial nerve palsy or Frey syndrome.